Mobile cooperative robotics through humanoid agent imitation (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2013)
This article presents a new development in cooperative robotics ba-sed on the imitation principle, in which a humanoid mobile agent actsas a master in the sequence of lateral displacement in order to movean objective load, coordinating other tree agents through zigbee com-munication, in a Token-ring network. The movement of every agentis determined by the gravity center (GC) and the movements reply ofthe master, in such a way that two of them acts by mirror imitationwhen confronting the master and the third one acts by direct imita-tion when standing on its side.
Keywords: cooperative robotics; Bioloid; imitation; inter-robot comunication